P35 Remote exercise testing can detect clinical change in pulmonary hypertension. (11th November 2022) - Stubbs, H; Jani, B; Brewis, M; Church, C; Johnson, M
Abstract : Background: The development of a set of remote exercise capacity tests for patients with pulmonary hypertension (PH) would improve the telemedicine strategies in this disease and allow remote patient assessment. The PH Remote Exercise Testing (PHRET) study is ongoing, assessing the validity and feasibility of tests when performed by patients at home. Aims: This interim analysis of PHRET data assesses the ability of remote exercise tests to detect clinical change following a period of treatment, as compared to change in the standard six-minute walk test (6MWT). Methods: Participants undergoing diagnostic assessment for PH were included. At baseline (visit 1), patients completed a 6MWT followed by a range of study tests including a Timed Up and Go (TUG) test, a Sit-to-Stand (STS), a Step Test (ST) and a 6MWT performed outside using a GPS-enabled smartphone (T6MWT). Patients performed these tests immediately upon returning home (visit 2) and at first follow-up (visit 3, usually ~3 months following treatment initiation). The proportion of change between visit 1 and visit 3 was compared to the change in the 6MWT. Results: At the time of writing, 49 patients are recruited and 25 have completed study follow up. Between visit 1 and 3 the mean (standard deviation) change in 6MWT distance was 26 m (62). Figure 1 demonstrates the proportion of change in each study test when compared to the 6MWT. Direction of change in the study test agreed with that in the standard 6MWT in 55% of the follow up ST, 63% of the STS, 32% of the TUG and 75% of the T6MWT. All patients were able to complete the study tests at home and no adverse incidents were recorded. Patients were able to record heart rate and finger oxygen saturations at home using pulse oximeters. Conclusions: These data raise the possibility that the T6MWT is the most effective remote measure of exercise capacity in patients with PH. The TUG demonstrated markedly inferior agreement. ST and STS showed less concordance than the T6MWT yet had greater than 50% agreement with the standard 6MWT.